Concerns and professional development needs of teachers at elementary schools in Saudi Arabia in adopting inclusive education - Asiri, Abdullah (Kansas State University, 2019)
This study reports an investigation of the concerns and professional development needs involved in adopting inclusive education and expressed by elementary school teachers in Saudi Arabia. The goal was to provide baseline information for the department of Planning and Development in the Ministry of Education for adopting inclusive education to increase the number of students with disabilities who receive appropriate special education services in regular classrooms. Participants in this research were special and general education teachers randomly selected from elementary schools in Riyadh, Saudi Arabia, that include special education programs. The theoretical framework of the study was the Concern Based Adoption Model (CBAM), and a non-experimental cross-sectional survey design was used to collect data. The data were obtained from 332 teachers, a response rate of 83%. The Stages of Concerns Questionnaire (SoCQ) provided by CBAM indicated that respondent stages of concern 0-2 (Unconcerned, Informational, and Personal) ranked highest, while stages 4-6 (Consequence, Collaboration, and Refocusing) ranked lowest. This profile was identified as a “nonuser profile”, meaning respondents wanted more information about inclusive education. A one-way MANOVA test revealed a statistically significant difference between respondent degree area and concerns about adopting inclusive education. Statistically significant differences were found in stages zero (Unconcerned), four (Consequence), five (Collaboration), and six (Refocusing). Furthermore, a t-test indicated that special education teachers are more concerned about inclusive education than general education teachers. Teachers in this study showed responses converging between agreement and disagreement, with slightly more respondents agreeing that administrators supported inclusive education. A statistically significant difference was found among teacher degree areas. Special education teachers tend to think administrator support for inclusive education is insufficient, while general education teachers tended to have no opinion about administrator support of inclusive education. In this study, teacher attitude towards inclusive education was positive with no statistically significant difference between teachers and their attitudes about adopting inclusive education. Teachers are in general show high desire for professional development on inclusive education, including immediate training and seminars/workshops on inclusive education. The only significant difference in desire for professional development was by gender. The t-test indicated that female teachers have more desire for professional development than male teachers.
Keywords: Inclusive education; Special education; General education; Elementary school; Concern based adoption model (CBAM)